Mombasa grass characterisation at different heights of grazing in an intercropping system with Babassu and monoculture - Rodrigues, Marcos Odilon Dias (2016)
The aim of this study was to evaluate agronomic and structural traits, as well as root mass, of Panicum maximum cv. Mombasa in different conditions of animal grazing in the same pasture in a monoculture system and a Pasture-Forestry Intercropping System (intercropped with Babassu palm trees). Evaluations were performed from December 2012 to February 2013. The systems were kept under continuous grazing with sheep (20 kg live weight on average) throughout the evaluation period. The design was completely randomised into split plots, in which each plot was the system and the subplots were grazing heights, with three sample cycles. The Babassu palm tree influenced the production of the aerial-part dry matter in the intercropping system due to a decrease in grass tillering caused by shading stress. The root dry matter decreased influenced by shading and intensity of animal grazing in the evaluated heights, leading to a reduction as decreased the grass height. The monoculture system led to better results for the same heights in all parameters in comparison to the intercropping system, including the number of tillers, dry matter production (DM), leaf-area index (LAI) and DM (%), which were higher in the monoculture system regardless of the assessed heights. The natural shade of Babassu palms negatively affected the productive and structural traits of Panicum maximum cv. Mombasa, thereby altering the grass structure and lowering its productive capacity.